Segmentasi Distributor Wilayah Temanggung Menggunakan Analisis Pareto dan Supplier Preferences : (Studi Kasus Pada Perusahaan Pia King Di Temanggung) - Dewi Hidayati; Hani Sirine (Universitas Wahid Hasyim, 2008)
This studies actually analyze distributor segmentation in Temanggung district by two types analysis such as Pareto and Supplier Preferences in Pia King Company Temanggung. The related study analyzed by Pareto Analysis and Supplier Preferences Analysis. Based on the result of analysis can take managerial decision. Thus through both of them the managerial decision is made.Keywords : Distributor segmentation, pareto analyis, supplier preferences analysis, and decision managerial